Water resource management through systemic approach: The case of Lake Bracciano. Issue 1 (3rd April 2021) - Armenia, Stefano; Bellomo, Davide; Medaglia, Carlo Maria; Nonino, Fabio; Pompei, Alessandro
ABSTRACT: Today natural water resources are becoming scarce, both due to global climate change but also due to irresponsible behaviour of human beings. Lakes are among the most delicate aquatic systems due to their limited size. The objective of this paper is to propose a System Dynamics model, employed in a real case study regarding the city of Rome and one of its water reserves, the Bracciano Lake, for the evaluation of different strategies and policies to reduce environmental impacts, considering different climatic and context scenarios. The results indicate that, as the system is currently exposed to a high risk of ecological disaster, the situation might worsen, and the disaster effectively happen. Simulation models may help agencies and administrations to explore policies and find solutions to address this fundamental problem, that may become even worst over the next years, given the potential severe consequences deriving from the current global warming trends.